Influence of Treatment with Sodium Benzoate and Packaging on quality of Catla (Catla catla) steaks during Chilled Storage - Jaydip G Kedar; Asif U Pagarkar; Nikheel Bhojraj Rathod; Taufin E Baug (Turkish Journal of Agriculture: Food Science and Technology, 2022)
Catla (Catla catla) steaks treated with sodium benzoate (SB) 0.5-2 % packed under aerobic (AP) and vacuum packaging (VP) were evaluated for biochemical, microbiological and sensory quality changes during chilled storage conditions for 27 days. The results were plotted against time, determining best fit order with corresponding regression equation to predict and compare with experimental findings. The formation of volatile amines (TVB-N) was low in samples treated with SB under VP, while no significant difference was observed in pH values. Peroxide value and salt soluble nitrogen values were significantly influenced under VP and SB treatment. Total plate count values significantly increased in all samples, but were within the maximum permissible limits. E. coli, S. aureus and Salmonella were not detected in the samples during storage. Zero order kinetics exhibited best fit for changes in biochemical and microbiological quality. Sensory evaluation scores had high correlation with storage period and low relative error (P0) for control samples under AP and VP. Therefore, combination of SB at 2.0% and VP can be used effectively as an intervention for the preservation of chilled stored Catla steaks.